O maragato beduíno: o conceito de gaúcho na escrita de Manoelito de Ornellas: The Bedouin maragato: the concept of gaucho in Manoelito de Ornellas (Revista de História da UEG (REVHIST), 2021)
This article proposes the study of the concept of gaucho in the writing of the story of Manoelito de Ornellas. The author's work taken as an object is Gauchos and Bedouins (1948). Methodologically, we opted for the contributions of the German historian Reinhart Koselleck, a reference in the area of ​​the History of Concepts. Initially, we present reflections on the concepts and the theory of the latter intellectual. Then, we present the institutional context in which Ornellas was inserted. Then, we demonstrate how the author conceived the concept of gaucho, as well as the reflexes of this in his writing of history. Finally, we draw some conclusions.Keywords: History of concepts. Gaucho. History of historiography.